(3SdGM GdeDef aj GdOYGA hGdPcQs - (3eMeO Hf eMeO Hf Ydj Hf geGe Hf GdGeGe, CHh YHO Gddg,J (B745 (3g` s
(3ChdgG (B:s
(3CeG HYO aef Chdi eG GfUQaJ Edi MaXg YfGjI Phi Gdgee s
(3BNQgG (B:s
(3SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd bGd Gddg jG GHf BOe Efc eG OYhJfi hQLhJfi ZaQJ dc Ydi eG cGf ajc hdG CHGdi jG GHf BOe dh CJjJfiJe GdcJGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B994s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(95) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs